Evolutionary paths of binaries with a neutron star – I. The case of SAX J1808.4 − 3658. Issue 1 (21st June 2018) - Tailo, M; D'Antona, F; Burderi, L; Ventura, P; di Salvo, T; Sanna, A; Papitto, A; Riggio, A; Maselli, A
ABSTRACT: The evolutionary status of the low-mass X-ray binary SAX J1808.4 − 3658 is simulated by following the binary evolution of its possible progenitor system through mass transfer, starting at a period of ∼6.6 h. The evolution includes angular momentum losses via magnetic braking and gravitational radiation. It also takes into account the effects of illumination of the donor by both the X-ray emission and the spin down luminosity of the pulsar. The system goes through stages of mass transfer and stages during which it is detached, where only the rotationally powered pulsar irradiates the donor. We show that the pulsar irradiation is a necessary ingredient to reach SAX J1808.4 − 3658 orbital period when the donor mass is reduced to 0.04–0.06 M⊙ . We also show that the models reproduce important properties of the system, including the orbital period derivative, which is shown to be directly linked to the evolution through mass transfer cycles. Moreover, we find that the effects of the irradiation on the internal structure of the donor are non-negligible, causing the companion star to be non-completely convective at the values of mass observed for the system and significantly altering its long term evolution, as the magnetic braking remains active along the whole evolution.